Sub-genotype phylogeny of the non-G, non-P genes of genotype 2 Rotavirus A strains. - Chantal Ama Agbemabiese (PLoS ONE, 2019)
Recent increase in the detection of unusual G1P[8], G3P[8], G8P[8], and G9P[4] Rotavirus A (RVA) strains bearing the DS-1-like constellation of the non-G, non-P genes (hereafter referred to as the genotype 2 backbone) requires better understanding of their evolutionary relationship. However, within a genotype, there is lack of a consensus lineage designation framework and a set of common sequences that can serve as references. Phylogenetic analyses were carried out on over 8,500 RVA genotype 2 genes systematically retrieved from the rotavirus database within the NCBI Virus Variation Resource. In line with previous designations, using pairwise comparison of cogent nucleotide sequences and stringent bootstrap support, reference lineages were defined. This study proposes a lineage framework and provides a dataset ranging from 34 to 145 sequences for each genotype 2 gene for orderly lineage designation of global genotype 2 genes of RVAs detected in human and animals. The framework identified five to 31 lineages depending on the gene. The least number of lineages (five to seven) were observed in genotypes A2 (NSP1), T2 (NSP3) and H2 (NSP5) which are limited to human RVA whereas the most number of lineages (31) was observed in genotype E2 (NSP4). Sharing of the same lineage constellations of the genotype 2 backbone genes between recently-emerging, unusual G1P[8], G3P[8], G8P[8] and G9P[4] reassortants and many contemporary G2P[4] strains provided strong support to the hypothesis that unusual genotype 2 strains originated primarily from reassortment events in the recent past involving contemporary G2P[4] strains as one parent and ordinary genotype 1 strains or animal RVA strains as the other. The lineage framework with selected reference sequences will help researchers to identify the lineage to which a given genotype 2 strain belongs, and trace the evolutionary history of common and unusual genotype 2 strains in circulation.